Community Perceptions Regarding the Implementation of the Role of Health Nurses at Program Achievement Levels - Wuriani, Wuriani; Djunaedi, Djunaedi; Carolina, Dina; Wahyudi, Ardi; Lukita, Yenni; Sriyanti, Febri (International Journal of Health Sciences, 2023)
Nursing services have an important role in the implementation of health services in public hospitals nationally. Success in a hospital depends greatly on the performance and role and function of nurses in providing nursing services. The role of nurses as Care Givers is to provide health services to individuals, families, groups and communities in the form of comprehensive nursing care which includes providing nursing care, providing direct assistance to individuals / patients and families / communities who experience problems with the need for security. Optimizing the role of nurses is very necessary where nurses must carry out their duties. The aim of this research is to determine public perceptions regarding this matter implementation of the role of nurses at the Tamalanrea Community Health Center. The design of this research is a descriptive survey method based on inclusion criteria. This research uses cluster sampling techniques and univariate analysis to analyze the data. The results show that the public has positive perceptions regarding several roles of nurses. Around 67% of the public have a positive perception of the role of nurses as educators. Therefore, it is hoped that nurses can improve their duties and functions as nurses and expand their role as nurses which still need improvements that have not been implemented well.